Combination of Empagliflozin and Linagliptin as Second-Line Therapy in Subjects With Type 2 Diabetes Inadequately Controlled on Metformin - DeFronzo, Ralph A.; Lewin, Andrew; Patel, Sanjay; Liu, Dacheng; Kaste, Renee; Woerle, Hans J.; Broedl, Uli C. (Diabetes care, 2015)
To evaluate the efficacy and safety of combinations of empagliflozin/linagliptin as second-line therapy in subjects with type 2 diabetes inadequately controlled on metformin. Subjects were randomized to a combination of empagliflozin 25 mg/linagliptin 5 mg (n = 137), empagliflozin 10 mg/linagliptin 5 mg (n = 136), empagliflozin 25 mg (n = 141), empagliflozin 10 mg (n = 140), or linagliptin 5 mg (n = 132) as add-on to metformin for 52 weeks. The primary end point was change from baseline in HbA1c at week 24. At week 24, reductions in HbA1c (mean baseline 7.90-8.02% [62.8-64.1 mmol/mol]) with empagliflozin/linagliptin were superior to those with empagliflozin or linagliptin alone as add-on to metformin; adjusted mean (SE) changes from baseline were -1.19% (0.06) (-13.1 mmol/mol [0.7]) with empagliflozin 25 mg/linagliptin 5 mg, -1.08% (0.06) (-11.8 mmol/mol [0.7]) with empagliflozin 10 mg/linagliptin 5 mg, -0.62% (0.06) (-6.8 mmol/mol [0.7]) with empagliflozin 25 mg, -0.66% (0.06) (-7.2 mmol/mol [0.7]) with empagliflozin 10 mg, and -0.70% (0.06) (-7.6 mmol/mol [0.7]) with linagliptin 5 mg (P < 0.001 for all comparisons). In these groups, respectively, 61.8, 57.8, 32.6, 28.0, and 36.1% of subjects with baseline HbA1c ≥7% (≥53 mmol/mol) had HbA1c <7% (<53 mmol/mol) at week 24. Efficacy was maintained at week 52. The proportion of subjects with adverse events (AEs) over 52 weeks was similar across treatment arms (68.6-73.0%), with no hypoglycemic AEs requiring assistance. Combinations of empagliflozin/linagliptin as second-line therapy for 52 weeks significantly reduced HbA1c compared with the individual components and were well tolerated.